Back Massage terhadap Nyeri dan Luaran Persalinan: Literature Review: Literature Review of Back massage Therapy on Labor Pain dan Outcomes - Ekadewi Retnosari (Universitas Ngudi waluyo, 2024)
One of the most common problems during labor is pain during contractions. There are many non-pharmacological interventions that are carried out, one of which is back massage. There has been a lot of research on back massage, therefore the researcher aims to find out literature reviews about the effect of back massage on pain and other outcomes of childbirth. The literature review method using the PRISMA approach was used in this literature review. Data synthesis uses the PICO method. Article sources used were Google Scholar, Pubmed NCBI and Scopus. The inclusion criteria set were articles with the keyword Back massage”.